Pelatihan Pembuatan Lilin Aromaterapi untuk Meningkatkan Kreativitas dan Jiwa Wirausaha Siswa SMA Veteran 1 Sukoharjo - Hanik, Nur Rokhimah; Wiharti, Tri; Nugroho, Anwari Adi; Sabrina, Mutia Zkiyyatun; Agustina, Melinda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This program aims to implement simple skills through aromatherapy candle making training for students of Veteran 1 High School, Sukoharjo. The urgency of this activity is to address the lack of practical skills and entrepreneurial spirit in the increasingly competitive field. The main problem of partners is the need for P5 programs and entrepreneurship subjects that can directly increase creativity and entrepreneurial spirit that has economic value. This training requires a small cost and simple equipment. The method used is a combination of training and skills, including socialization, demonstrations or direct practice. The targeted output is, an increase in understanding of how to make aromatherapy candles. From the results of the Aromatherapy Candle training for 12th grade Science program students, it was concluded that: The average understanding of students was categorized as very good, namely 88.82. There was an increase in understanding of the process of making aromatherapy candles on average from 52.76 to 88.82 or an increase of 74.74%. This community service activity succeeded in providing knowledge and practical skills to 12th grade Science program students of Veteran 1 High School, Sukoharjo.